Application of guided bone regeneration by placing chin block graft in the placement of implants - Rivas Sarmiento, Marco (2015)
Alveolar bone defects that result from the loss of a tooth, can hinder different dental procedures such as implants. In this situation, you can develop techniques to increase the alveolar ridge, either horizontally or vertically. Guided bone regeneration (GBR) is used since the 90s, based on the concepts of guided tissue regeneration, using a membrane that can generate better conditions for bone formation. In this case the clinical diagnosis, treatment planning, surgical technique and post-operative indications for improvement in the patient’s recovery, are developed.